2016
DOI: 10.1016/j.eururo.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Long Non-coding RNA SChLAP1 Independently Predicts Lethal Prostate Cancer

Abstract: The long noncoding RNA SChLAP1 is overexpressed in a subset of prostate cancers (PCa), and high SChLAP1 expression according to in situ hybridization (ISH) independently predicts biochemical recurrence after radical prostatectomy. Importantly, although biochemical recurrence is a significant clinical outcome, it is not a validated surrogate for PCa-related mortality. Thus, we evaluated the association between SChLAP1 expression and development of lethal PCa in a large cohort of American men with PCa and long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 10 publications
5
78
0
Order By: Relevance
“…An increasing amount of evidence has indicated that certain lncRNAs exhibit crucial roles in human cancers, acting as oncogenes or tumor suppressors (20,21). The lncRNA GAPLINC was previously reported to be overexpressed in gastric cancer and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence has indicated that certain lncRNAs exhibit crucial roles in human cancers, acting as oncogenes or tumor suppressors (20,21). The lncRNA GAPLINC was previously reported to be overexpressed in gastric cancer and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Representative photomicrographs of samples showing different MCPyV RNA-ISH intensities are illustrated in Supplementary Figure S1. As previously described, a cumulative ISH product score was calculated for each evaluable tissue core as the sum of the individual products of the expression level (0 to 4) and percentage of cells (0 to 100) (i.e., [ (22). For each tissue sample, the ISH product score was averaged across evaluable TMA tissue cores.…”
Section: Rna In Situ Hybridizationmentioning
confidence: 99%
“…SChLAP1, expressed at higher levels, has been proved to correlate with disease progression and poor outcome after radical prostatectomy in patients with localized PCa [109]. The test was validated in multi-institutional studies in predicting both metastases [34,110] and disease-specific survival [34,111]. Although clinical evidence on SChLAP1 in situ hybridization is being constantly updated, its prognostic features for prediction of pathologic outcome, metastases, BCR and survival have already been confirmed by meta-analysis [112].…”
Section: Schlap1 -Long Non-coding Rna Marks Lethal Pcamentioning
confidence: 99%